PERANCANGAN ANIMASI 3D LAGU DAERAH MALUKU - Alisa Aliah Mareta; Didit Prasetyo; Baroto Tavip Indrojarwo; Nugrahadi Ramadhani (Universitas Trisakti, 2022)
Abstract Design of 3D Serial Animation for Maluku Folk Songs. Indonesian folk songs, one of which is the Maluku folk song, are currently experiencing an existential crisis due to a decreasing interest by the younger generation because of modern pop culture entry. Preservation needs to be carried out by build interest and forming a listening habit to folk songs from an early age by targeting the younger generation, especially children, using modern/digital media like 3D animation that is preferable, entertaining, and easily accessible. The research process consists of experimental studies to produce scripts, characters, environments, storyboards, and animations. In-depth interviews with several animation experts to get input and corrections on created animation. Questionnaire as an animation test tool to get responses and from target audience. Based on the research results, the created animations have been successful in the aspects of the story, character design, and environment design. Keywords: 3d animation, Maluku folk songs, preservation Abstrak Perancangan Serial Animasi 3D Lagu Daerah Maluku. Lagu daerah Indonesia, salah satunya lagu daerah Maluku saat ini sedang mengalami krisis eksistensi akibat penurunan minat oleh generasi muda yang disebabkan masuknya budaya pop modern. Usaha pelestarian perlu dilakukan dengan cara menumbuhkan minat dan membentuk kebiasaan mendengarkan lagu daerah sejak dini dengan menargetkan generasi muda khususnya anak-anak, menggunakan media modern/digital seperti animasi 3D yang lebih disukai, menarik, dan mudah diakses. Proses riset terdiri dari studi eksperimental untuk menghasilkan rancangan desain naskah, karakter, environment, storyboard, dan animasi. Wawancara mendalam bersama beberapa ahli animasi untuk mendapatkan masukan dan koreksi atas animasi. Kuesioner sebagai alat uji animasi untuk mendapatkan respon dan penilaian dari taget audiens. Berdasarkan hasil riset, animasi yang dihasilkan sudah berhasil pada aspek cerita, desain karakter, dan environment. Kata kunci: animasi 3d, lagu daerah Maluku, pelestarian